2015
DOI: 10.1680/gein.14.00035
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and moisture effects on GCL and textured geomembrane interface shear strength

Abstract: This investigation was conducted to determine the effects of temperature and moisture on the shear strength of a double nonwoven geosynthetic clay liner (GCL) and a high-density polyethylene textured geomembrane (T-GM) interface for municipal solid waste landfills. Interface direct shear tests were conducted at normal stresses representative of cover liners (10, 20 and 30 kPa) and bottom liners (100, 200 and 300 kPa). Tests were conducted at temperatures of 2, 20 and 40°C (cover liner) and 20 and 40°C (bottom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…GCL internal strength was measured by direct shear, ring shear, and inclined plate [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The direct shear apparatus with displacement control and stress control has some advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…GCL internal strength was measured by direct shear, ring shear, and inclined plate [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The direct shear apparatus with displacement control and stress control has some advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…The existing test results have shown that the optimum range of temperature for the rapid degradation of organics is between 30°C and 40°C (Cecchi et al, 1993; DeWalle et al, 1978; Hartz et al, 1982). The degradation of organics in solid waste produces heat (El-Faddel et al, 1996; Faitli et al, 2015; Hanson et al, 2015; Hubert et al, 2016; Jafari et al, 2014; Meegoda et al, 2016; Pirt, 1978; Yasumasa et al, 2015; Yoshida and Rowe, 2003; Zanetti et al, 1997). The temperature in solid waste landfills varies in a wide range typically between 4°C and 50°C (Dach and Jager, 1995; Hanson et al, 2015; Jafari et al, 2014; Yoshida and Rowe, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The degradation of organics in solid waste produces heat (El-Faddel et al, 1996; Faitli et al, 2015; Hanson et al, 2015; Hubert et al, 2016; Jafari et al, 2014; Meegoda et al, 2016; Pirt, 1978; Yasumasa et al, 2015; Yoshida and Rowe, 2003; Zanetti et al, 1997). The temperature in solid waste landfills varies in a wide range typically between 4°C and 50°C (Dach and Jager, 1995; Hanson et al, 2015; Jafari et al, 2014; Yoshida and Rowe, 2003). It may even rise above 70°C (Lefebvre et al, 2000), at which the degradation of organics would be inhibited.…”
Section: Introductionmentioning
confidence: 99%
“…Vukelic et al (2008) reported bentonite extrusion to be more extensive during shearing of prehydrated GCL/GM than for non-prehydrated GCL/GM interfaces. Hanson et al (2015) identified threshold water contents and normal stress levels for onset of significant bentonite extrusion. In addition, fluid transfer characteristics of GCLs (i.e., containment effectiveness) are expected to be affected by bentonite extrusion due to the resulting reduction in the amount of bentonite in GCLs.…”
Section: Introductionmentioning
confidence: 99%